Penggunaan Media Game Digital pada Anak Usia Dini - Layinatul Muarifah; Nunuk Suryani; Gunarhadi Gunarhadi (Teknodika, 2017)
The development of the globalization era is inseparable from technological developments. The use of gadgets has become a natural phenomenon that can be found at all levels of age, from an early age to old age. Gadgets are used with a variety of purposes, ranging from establishing social contact with others, as a learning medium, to using them as entertainment. The purpose of this study was to determine the nature of digital games and analyze their use in early childhood as a medium of learning. This research is qualitative research which uses a literature study as a method of collecting data and is then used as part of a study introduction to further develop research with the same title theme. The research subjects were children aged 4-5 years. The results showed that digital games are digital devices that allow users to have fun with rules that have been designed in such a way and can be used as learning media for educational functions. Early childhood has been able to use the game as a medium for playing. Even though they have been used to using games, but as a learning medium for educational functions, games are still somewhat unfamiliar to be used in kindergarten education. This is proven by the lack of research that mentions the use of media games at the level of kindergarten education. Seeing the many benefits of game media that can be obtained, the game as a learning media needs to be further developed into an effective learning media for early childhood and in accordance with the learning objectives